Urgensi Reformulasi Undang-Undang Informasi dan Transaksi Elektronik terhadap Penyalahgunaan Kecerdasan Buatan Deepfake dalam Perspektif Pembaharuan Hukum Pidana - Bintang muhammad Akbar; Rena Yulia; Muhamad Romdoni (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The rapid advancement of artificial intelligence, particularly deepfake technology, has generated complex challenges for criminal law enforcement in Indonesia. Deepfake technology enables highly realistic manipulation of audio-visual content, increasing the risk of defamation, fraud, disinformation, identity misuse, and other forms of cybercrime. Although the Indonesian Law on Electronic Information and Transactions (ITE Law) regulates electronic information and data manipulation, its provisions remain general and have not explicitly addressed the specific characteristics, risks, and legal implications of AI-generated synthetic content. This normative gap has led to legal uncertainty, difficulties in criminal qualification, challenges in digital evidence verification, and ambiguity in determining criminal liability, especially in cases involving deepfake-based hoaxes. Through a normative juridical analysis supported by statutory, conceptual, and comparative approaches, this article highlights the limitations of the current ITE Law framework in responding to the evolving nature of deepfake misuse. Comparative insights from the European Union’s AI Act and China’s Deep Synthesis Provisions demonstrate more adaptive, risk-based, and preventive regulatory models. The findings underline the urgency of reformulating the ITE Law to explicitly regulate deepfake content, strengthen legal certainty, integrate preventive mechanisms such as transparency and platform responsibility, and align criminal law policy with technological developments. Such reformulation is essential to ensure effective law enforcement, protect fundamental rights, and maintain public trust in the digital ecosystem..